Complete cystic fibrosis transmembrane conductance regulator gene sequencing in patients with idiopathic chronic pancreatitis and controls. Issue 10 (29th June 2005) - Weiss, F U; Simon, P; Bogdanova, N; Mayerle, J; Dworniczak, B; Horst, J; Lerch, M M
Abstract : Background: Mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) gene—many of which cause cystic fibrosis—have also been reported in patients with chronic pancreatitis. The authors examine whether mild or severe CFTR mutations, homozygous or compound heterozygous CFTR mutations, or even simple cystic fibrosis carrier status alone increases the risk of developing pancreatitis. Methods: After exclusion of patients with trypsinogen (PRSS1) mutations, cystic fibrosis, or pulmonary disease, and with known risk factors for pancreatitis 67 patients with idiopathic chronic pancreatitis (ICP) from northwest Germany and 60 geographically and ethnically matched controls were recruited. The entire coding region of the CFTR gene was sequenced in all patients and controls. ICP patients were also analysed for serine protease inhibitor Kazal type 1 (SPINK1) gene mutations. Results: Abnormal CFTR alleles were found to be twice as frequent in ICP patients as in controls (25/134 v 11/120; p<0.05). Three of four severe CFTR mutations detected in patients were compound heterozygous with another abnormal CFTR allele, whereas among controls three severe CFTR mutations were found in heterozygous cystic fibrosis carriers. In ICP patients 19 uncommon/mild mutations, including combinations of the 5T allele with 12TG repeats, were identified compared with only five in controls (p = 0.012). Heterozygous SPINK1 mutations were detected in eight ICP patients (15% v 1% in controls) but only one also carried an additional mild CFTR mutation. Conclusions: These data show that not only compound heterozygosity, but also cystic fibrosis carrier status for different types of CFTR mutations, including uncommon/mild mutations, significantly increase the risk of developing pancreatitis. Although 45% of the study's ICP patients carried predisposing genetic risk factors (for example, mutations in CFTR or SPINK1), the authors found no evidence that the risk conveyed by CFTR mutations depends on co-inherited SPINK1 mutations.